Perancangan Sistem Informasi Akademik Universitas Negeri Wakanda - Hartini Ramli; Fitrawati Surya Yusuf; Muh Kholil Gibran; Muh Syahrul Musfat Pratama; Surianto Mappangara (Sakura Digital Nusantara, 2024)
In this fast-paced era, universities need to update their management systems with an integrated academic information system. The use of web-based academic information systems has become increasingly important and is considered essential for universities today. This research aims to develop a web-based academic information system at Wakanda State University in order to optimize data management and academic activities in higher education institutions. The research method employed includes literature review and system development using a prototype model. In the literature review phase, data is gathered from various sources such as national and international journals. System development follows a prototype model involving steps such as identifying needs, building prototypes, testing the system, evaluating the system, and implementing the system. The findings of this research are expected to result in an integrated and effective web-based academic information system at Wakanda State University.